Synergistic mechanical response of Nylon 6/Trogamid (R) T blends - Ridhore, Amol; Jog, Jyoti Prakash (Journal of Applied Polymer Science, 2013)
Blends of semicrystalline Nylon 6 with a varying ratios of amorphous Nylon are studied for their morphological, thermal, dielectric, and mechanical behavior. Thermal analysis indicated a compositional dependant decrease in the melting and crystallization temperatures of Nylon 6. The blends exhibited a single compositional dependant glass transition temperature in dynamic mechanical thermal analysis and dielectrical relaxation spectroscopy over entire mixing ratio indicating miscibility between the blend components. The values of flexural modulus and tensile modulus of the blends are found to increase without significant loss in the impact properties. The water absorption of the blends is also lower than the values calculated by rule of mixtures. The observed synergistic behavior of the mechanical properties of the blends is indicative of presence of strong interactions in the blends components. (c) 2012 Wiley Periodicals, Inc. J. Appl. Polym. Sci., 2013
Keywords: blends; dielectric properties; mechanical properties; polyamides; Thermal properties